Disfunción ejecutiva en la Enfermedad de Huntington en fase preclínica versus fase clínica - Radulovich Muñoz, Milena (2019)
Huntington's disease has been studied largely by its motor symptomatology, but cognitive and psychiatric affections appear to years before the motor debut. Neuropsychiatric symptoms represent an important load for patients and their families for the loss of independence of those who suffer them. The objective of this work is to carry out a research of the specific cognitive symptoms that differ them to carry out only the basic daily activities, the references to the executive system. By identifying the main affections of patients from early stages, a more efficient therapeutic approach can be designed. The review was carried out with studies of the last six years, that were empirical studies and that included patients with the grouped disease according to its evolution. Within the studies used, different methods of evaluation of the executive system applied. Both psychiatric and cognitive symptoms are valued within the executive function and how they evolve in the course of disease. The results point out to an important executive dysfunction from initial stages of the disease, in particular an increased risk of apathy since very early in the situation.